Dermoscopy could be useful in differentiating sarcoidosis from necrobiotic granulomas even after treatment with systemic steroids - Shahira Ramadan; Dalia Hossam; Marwah A. Saleh (Mattioli1885, 2016)
Background: Diagnosing cutaneous sarcoidosis and necrobiotic granulomas is challenging. Objective: Assessing the value of dermoscopy in differentiating cutaneous sarcoidosis from necrobiotic granulomas and evaluating whether their dermoscopic features will be altered after treatment. Methods: Nineteen cutaneous sarcoidosis and 11 necrobiotic granuloma patients (2 necrobiosis lipoidica, 4 granuloma annulare and 5 rheumatoid nodule) were included in this study. The diagnosis was confirmed by skin biopsy. The lesions were examined using non-contact polarized dermoscope (Dermlite 2 HR-Pro; 3Gen, San Juan Capistrano, CA). Results: Ten out of 19 cutaneous sarcoidosis patients and 7/11 necrobiotic cases group were receiving treatments (topical, intralesional or systemic steroids ± chloroquine) but still have cutaneous lesions. Treatment duration in the sarcoidosis group ranged from 2 months to 10 years (median 3 years) and in the necrobiotic cases group ranged from 3 months to 16 years (median 2 years). Pink homogenous background, translucent orange areas, white scar-like depigmentation and fine white scales were significantly associated with the cutaneous sarcoidosis compared to necrobiotic cases group. On the other hand mixed pink, white and yellowish background was significantly associated with the necrobiotic cases group. No significant difference in the dermoscopic findings was detected between treated and non-treated patients. Conclusion: Some dermoscopic findings are shared between the cutaneous sarcoidosis group and the necrobiotic cases group, yet dermoscopy could be a useful aid in differentiating them even after treatment.